A case of brain abscess caused by actinomyces mimicking glioma: A rare presentation (Indian Journal of Case Reports, 2019)
Actinomycosis is a rare, chronic and slowly progressive granulomatous disease, caused by filamentous Gram-positive anaerobic bacteria from Actinomycetaceae family (genus Actinomyces) belonging to endogenous flora of mucous membranes. Actinomycosis infection to the Central Nervous System is generally secondary to hematogenous dissemination from the primary infection in the lung, abdomen, pelvis or by continuity in a cervical, oral or facial infection, since it is closely related to mycobacteria in the mouth and gastrointestinal tract. Actinomyces abscess of the brain can at times be confused with space-occupying lesions (SOL), tuberculosis as was seen in this case. A biopsy is essential for the diagnosis as if treated early these patients have a good prognosis. We present a case of 28 years male presented with frontal SOL which came out as actinomycosis on biopsy.